2011
DOI: 10.2478/s11756-011-0102-6
|View full text |Cite
|
Sign up to set email alerts
|

Phenolic content and antioxidant activity in two contrasting Medicago ciliaris lines cultivated under salt stress

Abstract: The objective of this study was to determine more indepth physiological and antioxidant responses in two Medicago ciliaris lines (a salt-tolerant line TNC 1.8 and a salt-sensitive line TNC 11.9) with contrasting responses to 100 mM NaCl. Under salt stress, both lines showed a decrease in total biomass and in the growth rate for roots, but TNC 1.8 was less affected by salt than TNC 11.9 in that it maintained leaf growth even in the presence of added salt. In both lines, salt stress mainly affected micronutrient… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 51 publications
0
2
0
Order By: Relevance
“…The differential accumulation of phenolic fractions under different salt treatments in the plant species with different salinity resistance suggests that salt resistant species and varieties may employ phenolic compounds, especially phenolic acids and flavonoids differentially to adapt to contrasting salinities (Mahmoudi et al, 2010). This phenomenon was confirmed by Salah et al, (2011) who reported that The salt-tolerant Medicago ciliaris line TNC 1.8 was more efficient at managing salt-induced oxidative damage in leaves and in roots than the saltsensitive line TNC 11.9, by preserving higher phenolic compound levels in both organs. In sugarcane and maize, similarly, salt tolerant varieties were found to accumulate significantly higher amount of soluble phenolics, anthocyanins, flavones and several polyphenols under salt stress conditions while content of the same metabolites decreased in response to salt treatment in case of salt sensitive varieties of both species (Wahid and Ghazanfar, 2006).…”
Section: Resultsmentioning
confidence: 78%
“…The differential accumulation of phenolic fractions under different salt treatments in the plant species with different salinity resistance suggests that salt resistant species and varieties may employ phenolic compounds, especially phenolic acids and flavonoids differentially to adapt to contrasting salinities (Mahmoudi et al, 2010). This phenomenon was confirmed by Salah et al, (2011) who reported that The salt-tolerant Medicago ciliaris line TNC 1.8 was more efficient at managing salt-induced oxidative damage in leaves and in roots than the saltsensitive line TNC 11.9, by preserving higher phenolic compound levels in both organs. In sugarcane and maize, similarly, salt tolerant varieties were found to accumulate significantly higher amount of soluble phenolics, anthocyanins, flavones and several polyphenols under salt stress conditions while content of the same metabolites decreased in response to salt treatment in case of salt sensitive varieties of both species (Wahid and Ghazanfar, 2006).…”
Section: Resultsmentioning
confidence: 78%
“…Plants respond to stress by increasing the antioxidant activity to restore the cellular equilibrium between production and scavenging of ROS (Salah et al 2011;Bano et al 2014). Decreased antioxidant activity can lead to overproduction of ROS and lipid peroxidation of cell membranes, which would result in harmful ion leakage.…”
Section: Resultsmentioning
confidence: 99%